Reconstruction of Public Sector Accounting as a Good Governance Instrument in Strengthening Government Accountability - Nafisah Zehny; Indah Fajarini (Lembaga Riset Ilmiah, 2026)
Public sector accounting plays a strategic role in realizing good governance through strengthening transparency and accountability in the management of public finances. However, various cases of corruption, limited budget transparency, and weak public accountability indicate that the current implementation of public sector accounting has not been able to optimally support good governance practices. Previous studies have generally focused on the administrative and financial reporting functions of public sector accounting, while studies that specifically examine the reconstruction of public sector accounting as an instrument for strengthening governmental accountability remain limited. Based on this research gap, this study aims to analyze the role of public sector accounting in supporting the principles of good governance and to formulate a reconstruction model of public sector accounting that is more substantively oriented toward accountability. This study employs a qualitative method with a descriptive-critical approach through a literature review and the analysis of various public financial management phenomena. The findings reveal that current public sector accounting practices tend to be administrative, formalistic, and compliance-oriented, thereby limiting their ability to promote substantive accountability effectively. The novelty of this study lies in the development of a reconstructed public sector accounting framework that positions accounting not merely as a financial reporting instrument but also as a mechanism for public oversight and the strengthening of governance. This reconstruction is carried out through enhancing digital transparency, optimizing internal control systems, internalizing ethical values and integrity among public officials, and increasing public participation in the oversight of public finances. The study demonstrates that strengthening governmental accountability cannot be achieved solely through improvements in financial reporting systems; rather, it requires the transformation of public sector accounting into a strategic instrument that supports transparency, participation, and accountability in public administration.